Surviving the Cultural Shock During Cultural Immersion: an EFL Teacher in CELTA Program - Eni Uswatun Hasanah; Ita Arfyanti; Jihan Nabilah (Poltanesa, 2026)
This study aims to examine an Indonesian EFL teacher's experiences and coping strategies while enrolled in the CELTA program, with an emphasis on how the teacher handled cultural shock. The study uses a case study methodology, and semi-structured interviews are used to collect data. The findings reveal that the teacher went through several stages of cultural shock, including the honeymoon stage, the stage of negotiations, and the stage of adjustment. The teacher used a variety of coping strategies, including asking for help from peers, honing her language abilities, and researching the host culture. This study highlights the value of cultural sensitivity and awareness in EFL teacher preparation programs and provides helpful advice for other EFL instructors who may experience cultural shock while teaching abroad.